Experimental Study to Investigate the Effect of Polyacrylamide Gel to Reduce the Lost Circulation - K. Al-Delfi , Ali; Al-Mahdawi, Faleh H. M.; Mukhtar, Yasir; Eltahir Bagadi, Yousif (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
One of the challenging issues encountered during drilling operations is the lost circulation. Numerous issues might arise because of losses, such as wasting of time and higher drilling cost. Several types of lost circulation materials have been developed and are being used to limit mud losses and avoid associated issues. Each solution has benefits and drawbacks.In this study, a core flooding test was performed to study the effectiveness of polyacrylamide (PAM) granular gel on the reduction of the circulation lost. One common type of fracture characteristic is fractures with tips, commonly known as partially open fracture (POF). However, PAM gel therapy in POFs received little attention in prior research. Models of partly open fractures were built using a cylindrical core. A series of processes are performed on a core to get a POF model. Overall, the PAM gel can decrease plug permeability, making it a useful material for lost circulation. The results indicate that the Polyacrylamide granular gel can decrease the permeability up to 193 times.